2004
DOI: 10.1097/01.hjr.0000114968.39211.01
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative meta-analysis of prospective studies of plasma fibrinogen and cardiovascular disease

Abstract: A central database has been established containing data on plasma fibrinogen, sex and other potential confounding factors, age at baseline fibrinogen measurement, age at event or at last follow-up, major vascular morbidity and cause-specific mortality. Information about any repeat measurements of fibrinogen and potential confounding factors is being sought to allow study-specific correction for regression dilution. The analyses will involve age-specific regression models. Synthesis of the available prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Fibrinogen is a soluble glycoprotein with a molecular weight of 340 kDa, which consists of three polypeptide chains. It is the precursor of fibrin and acts as a pivotal determinant of blood viscosity, platelet aggregation, fibrin formation, subsequent coagulation activation and fibrinolysis [20] . More recent work has shown that as fibrinogen level increased above physiologic levels, the balance between clotting and fibrinolysis is shifted toward the former [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen is a soluble glycoprotein with a molecular weight of 340 kDa, which consists of three polypeptide chains. It is the precursor of fibrin and acts as a pivotal determinant of blood viscosity, platelet aggregation, fibrin formation, subsequent coagulation activation and fibrinolysis [20] . More recent work has shown that as fibrinogen level increased above physiologic levels, the balance between clotting and fibrinolysis is shifted toward the former [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Prospective epidemiological studies ( 3 6 ) and meta-analyses ( 29 31 ) clearly indicate that fibrinogen was an independent risk factor for adverse cardiovascular events, similar in incidence to other major risk factors such as cholesterol and smoking ( 3 6 ). In addition, studies have reported an association between fibrinogen and the presence and severity of ISR, suggesting its potential role in the progression of coronary atherosclerosis ( 7 , 8 , 32 ).…”
Section: Discussionmentioning
confidence: 98%
“…For example, the meta-analyses by ERFC included data from 12–68 studies for each biomarker even though there are currently over 100 studies included in this collaboration 5960 61 In fact, biomarkers examined in large consortia are among the most studied and “hottest” biomarkers in the medical literature—such as C reactive protein, fibrinogen, and lipid related markers. Selection forces might be affecting some of those particular biomarkers to a greater extent and may not be fully remedied even with meticulous standardisation of data contributed to a retrospective consortium such as ERFC 62…”
Section: Discussionmentioning
confidence: 99%